Proof Of Grant That Violates Legitieme Portie According To Civil Code - Mahalia Nola Pohan, Nita Nilan Sry Rezki Pulungan (NOMOI Law Review, 2020)
Grantas mentioned in Article 1666 of the Civil Code, is"Something of agreement with which the donor in his lifetime, with Free and irrevocably, surrender an object for the needs of the recipient of the grant receiving the surrender.But in practice, the grantoroften gives his assets more than his wealth, or exceeds the port specified by the Law, so that inheritance disputes arise by heirs.To prove a grant made by the testator had violatedlegitieme portieor not is todetermine the overall numberboedelinheritance, thenwillbe calculatedlegitieme portieit.This paperwilldiscuss proof of legitimie portie grant violations committed by the testator and efforts to protect the rights of heirs in the grant so that they do not violate the Civil Code.This paper is conducted using normative juridical research methods or library law research, the method or method used in legal research conducted by examining existing library materials.Prove that a grant made by the testator had violatedlegitieme portieis todetermine the overall numberboedelinheritance, and then countedlegitieme portieit, after it was discovered the magnitude oflegitieme portiethen be seen how much the remaining estate after the grant implemented.Keywords:Proof, Legitieme Portie, Grant.